On the Phonological Derivation of Compensatory Lengthening in Standard Malay: A Stratal Optimality Theoretical Approach - ALQAHTANI, MUFLEH (International Journal of Language and Literary Studies, 2022)
This study used Stratal Optimality Theory (OT) as the analytical framework to analyze the phonological derivation of Compensatory Lengthening (CL) in Standard Malay that targets the moraic rhotic /r/ in the coda position. It was concluded that to ensure the moraicity assignment to the rhotic /r/ in the postvocalic position before any consonant deletion or vowel lengthening, the moraic structures were built based on Weight-By-Position (WBP) prior to the segmental changes that resulted in the CL, which meant that the floating mora became affiliated to the preceding stem vowel. This phonological derivation was seen to be a form of counterbleeding in which the consonant deletion counterbleeds the WBP. The Stratal OT model successfully accounts for this counterbleeding as an opaque rule interaction, with the first stratum ensuring that the moraic structure is built before any segmental deletion or lengthening changes and the second stratum dealing with the CL.